The Influence of Work Discipline and Work Experience on Employee Performance of PT. Indonesian Classification Bureau Tanjung Perak Main Branch Surabaya - Syifana, Ananda Azza; Iryanti, Endang (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this study is to investigate the relationship between PT. Indonesian Classification Bureau Tanjung Perak Surabaya staff' performance and their job experience and discipline. The research methodology employed in this study is associative analysis in quantitative research. Saturated sampling procedures were used in this study, which included 46 employees of the PT. Indonesian Classification Bureau Tanjung Perak Surabaya as the population and sample. The analysis procedure makes use of the Partial Least Squares (PLS) analysis technique. Work experience and work discipline have an impact on employee performance at the main branch of PT. Indonesian Classification Bureau Tanjung Perak Surabaya. So that the company can grow, it is intended that this involvement would have a favorable effect on employee performance in the future.